EVALUASI PELAKSANAAN PEMBELAJARAN DARING DITINJAU DARI STANDAR PROSES PEMBELAJARAN: (Studi Kasus di SMA Negeri 1 Getasan, Kab. Semarang) - Andharweni, Theresia Ayu (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Satya Wacana, 2022)
The Covid-19 pandemic has also affected the process of implementing learning in schools, including at SMA Negeri 1 Getasan. The purpose of this study was to evaluate the online learning process at SMA Negeri 1 Getasan in the first semester of the 2021-2022 academic year in terms of the fulfillment of the learning process standards set through Permendikbud No. 22/2016, and to formulate practical recommendations to improve the performance of the learning implementation process. which is held online for SMA Negeri 1 Getasan, Semarang Regency, especially in the subject of Economics. The research method used in this study is a qualitative research method, with data collection techniques using observation, interviews and documentation studies, as well as data processing techniques using interactive analysis models. The unit of observation in this study were all subject teachers, with the unit of analysis being Economics subject teachers. The results of the study indicate that the planning, implementation, process and outcome assessment processes, as well as learning supervision in general have been carried out in accordance with the standards of the learning process. However, there are some technical obstacles faced by teachers and students in an effort to implement interactive and effective learning, especially in the aspects of technology and information, as well as the availability of supporting facilities.